Analisis Penawaran Tenaga Kerja di Sumatera Barat - Annisyah Putri Ardi; Yulhendri Yulhendri (Jurnal Ecogen, 2019)
The purpose of this study was to analyze the demand and supply of labor in West Sumatra. This study used secondary data using a total of 19 objects by district / city in West Sumatra (2013-2017). Data analysis technique used was panel data analysis using eviews 9. The data analysis technique used is panel data analysis using eviews 9. Based on the analysis results it was found that wages do not have a significant positive effect and GRDP has a significant positive effect on labor supply. Keyword: supply of labor. wage, gdp